Reconstruction of the maxilla following hemimaxillectomy defects with scapular tip grafts and dental implants - Mertens, Christian; Freudlsperger, Christian; Bodem, Jens; Engel, Michael; Hoffmann, Jürgen; Freier, Kolja (Journal of cranio-maxillofacial surgery, 2016)
Treatment of post-resective defects of the maxilla can be challenging and usually requires dental obturation or microvascular reconstruction. As compared to soft-tissue microvascular grafts, bone reconstruction can additionally allow for facial support and retention of dental implants. The aim of this study was to evaluate scapular tip grafts with respect to their applicability for maxillary reconstruction and their potential to retain dental implants for later dental rehabilitation. In this retrospective study, 14 patients with hemimaxillectomy defects were reconstructed with free scapular tip grafts, oriented horizontally, to rebuild the palate and alveolar ridge. After bone healing, three-dimensional virtual implant planning was performed, and a radiographic guide was fabricated to enable implant placement in the optimal anatomic and prosthetic position. All patients' mastication and speech were evaluated, along with the extent of defect closure, suitability of the graft sites for implant placement, and soft-tissue stability. Pre- and postsurgical radiographs were also evaluated. A good postoperative outcome was achieved in all patients, with complete closure of maxillary defects that were class II, according to the system of Brown and Shaw. Additional bone augmentation was necessary in two patients in order to increase vertical bone height. Patients were subsequently treated with 50 dental implants to retain dental prostheses. In all cases, additional soft-tissue surgery was necessary to achieve a long-term stable periimplant situation. No implants were lost during the mean observation period of 34 months. Due to its specific form, the scapular tip graft is well suited to reconstruct the palate and maxillary alveolar ridge and to enable subsequent implant-retained rehabilitation. Due to the limited bone volume, an accurate three-dimensional graft orientation is essential. Furthermore, most cases require additional soft-tissue surgery to achieve a long-term stable periimplant situation.